2005
DOI: 10.1094/pd-89-0012
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Nattrassia mangiferae Root and Stem Rot Pathogen of Cassava in Bénin

Abstract: Root rot pathogens were found through diagnostic surveys in all departments (regions) of Bénin, West Africa, to affect 86 to 100% and 96 to 100% of cassava fields during the dry and rainy seasons, respectively. Disease incidence in individual fields ranged between 0 and 53%, and averaged 16 to 27% per department. Nattrassia mangiferae was consistently the most frequently isolated root rot pathogen (56% in the dry season and 22 to 52% in the rainy season). Pathogenicity of N. mangiferae was confirmed on four cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Since rot diseases occur underground where they are not visible, their impact is not as readily perceived as are those caused by foliar pathogens. Cassava plants are quite resilient and have an extensive root system that enables the plant to remain standing and asymptomatic even when heavily infected (18), which further masks the effect of root rotting pathogens until the tubers are harvested. Based on surveys of farmers in the humid forest area of Cameroon, 58% of the sampled population (n = 120) ranked root rot disease as the main constraint to cassava production (M. Mwangi, R. Bandyopadhyay, and C. Nolte, unpublished data).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since rot diseases occur underground where they are not visible, their impact is not as readily perceived as are those caused by foliar pathogens. Cassava plants are quite resilient and have an extensive root system that enables the plant to remain standing and asymptomatic even when heavily infected (18), which further masks the effect of root rotting pathogens until the tubers are harvested. Based on surveys of farmers in the humid forest area of Cameroon, 58% of the sampled population (n = 120) ranked root rot disease as the main constraint to cassava production (M. Mwangi, R. Bandyopadhyay, and C. Nolte, unpublished data).…”
mentioning
confidence: 99%
“…Disease incidence usually is higher during the rainy season, but some pathogens, e.g., Macrophomina phaseolina, are more common during the dry season (18). The main symptom of rot disease is a breakdown in tissue of the mature tuberous roots, usually associated with a foul odor and changes in color, which may be useful in distinguishing the pathogens involved.…”
mentioning
confidence: 99%
“…It was reported to cause about 20 to 80% yield loss (Mskita et al, 2005). Aigbe and Remison (2010) reported that the starch content and quality of garri decreased with increasing incidence or severity of root rot among assessed varieties of cassava.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is caused by different root rot fungi, and has been reported to cause yield losses of up to 80% in farmers' fields (Msikita et al, 2005). Because the rot pathogens affect the underground tuberous roots of cassava, the magnitude of the damage cannot be quantified until harvest.…”
Section: Introductionmentioning
confidence: 99%
“…as the most important pathogens of this disease in the region (Msikita et al, 1998(Msikita et al, , 2005Onyeka et al, 2004). In a comprehensive survey across cassava ecological zones in Nigeria, B. theobromae was observed in more than 70% of 115 farmers' fields (Onyeka, 2002).…”
Section: Introductionmentioning
confidence: 99%